Complete chloroplast genome sequence of the medical fern Drynaria roosii and its phylogenetic analysis. Issue 1 (1st January 2017) - Sun, Meiyu; Li, Jingrui; Li, Dong; Shi, Lei
Abstract: In this study, the complete chloroplast genome of the medical fern Drynaria roosii was completed and analyzed in order to understand the evolution of the genome of the fern lineages. In D. roosii, the circular double-stranded cpDNA sequence of 154, 305 bp consists of two inverted repeat (IRA and IRB) regions of 23, 416 bp each, a large single-copy (LSC) region of 86, 040 bp and a small single-copy (SSC) region of 21, 433 bp. The overall GC content is 40.92% and the GC contents of LSC, IRs, and SSC are 39.75%, 45.07%, and 36.60%, respectively. D. roosii with 108 annotated unique genes included 85 protein-coding genes, 19 tRNA genes, and 4 rRNA genes. Using the whole chloroplast genome sequences alignment of 18 species from ferns, the phylogenetic relationship was built. The phylogenetic position of D. roosii was closely clustered with Adiantum capillus-veneris, Cheilanthes lindheimeri, and Pteridium aquilium subsp . Aquilinum as sister species and then clustered with Alsophila spinulosa, Lygodium japonicum, Diplopterygium glaucum, and Osmundastrum cinnamomeum . D. roosii belongs to Polypodiales . The complete chloroplast genome of D. roosii provides utility information for ferns evolutionary and genomic studies.